Rainwater Harvesting for Increased Pasture Production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
This leaflet describes one method of rainwater harvesting – using hoops. This method is particularly suited to pasture production in dry areas.